PENGARUH FINANCIAL LITERACY, PENGETAHUAN DAN MOTIVASI INVESTASI MAHASISWA TERHADAP PEMANFAATAN PELUANG INVESTASI DI MASA PANDEMI COVID-19 (Studi Empiris Pada Mahasiswa Akuntansi FEB Unisma) - Deby Septiani Putri; Nur Diana; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the effect of financial literacy, knowledge, and student investment motivation on the utilization of investment opportunities during the COVID-19 pandemic. The research sample was 284 accounting students from FEB Unisma and obtained data using a questionnaire using google form. The results of this study are that there is a significant influence of financial literacy, knowledge, and investment motivation on the utilization of investment opportunities during the COVID-19 pandemic. partially financial literacy has a significant positive effect on the utilization of investment opportunities during the covid-19 pandemic. partially knowledge has a significant positive effect on the utilization of investment opportunities during the covid-19 pandemic. and lastly, partially student investment motivation has a significant positive effect on the utilization of investment opportunities during the covid-19 pandemic. Keywords : financial literacy, Knowledge, Investment Motivation, Utilization, Investment Opportunities Covid-19